2006
DOI: 10.3892/ijo.28.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Enteral (oral or tube administration) nutritional support and eicosapentaenoic acid in patients with cancer: A systematic review

Abstract: Abstract. The aim of this systematic review was to determine the efficacy and potential benefits of enteral nutritional support [oral nutritional supplements (ONS) or enteral tube feeding (ETF)], and eicosapentaenoic acid (EPA, free acid, ethyl esters or fish oil; provided as capsules or enriched ONS or ETF) in patients with cancer. Clinical studies were identified using electronic databases, and studies were selected according to predetermined criteria. For each treatment modality (chemo/radiotherapy, surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 78 publications
(293 reference statements)
7
73
0
10
Order By: Relevance
“…These findings were confirmed in a more recent metaanalysis of RCT in cancer patients by Elia et al (29) .…”
Section: Comparing Parenteral With Enteral Nutritionsupporting
confidence: 61%
“…These findings were confirmed in a more recent metaanalysis of RCT in cancer patients by Elia et al (29) .…”
Section: Comparing Parenteral With Enteral Nutritionsupporting
confidence: 61%
“…Several systematic reviews and meta-analyses have examined the role of omega-3 fatty acids in preventing cancer-related cachexia [163][164][165]. The strictest of the three only includes five studies and suggests that the literature is insufficient to judge whether eicosapentaenoic acid (EPA) is superior to placebo in treating cachexia.…”
Section: Cachexiamentioning
confidence: 99%
“…Heterogeneity existed in the composition of the x3FA supplements and the mode of delivery, but lower fat formulas appeared to be better tolerated. Looking specifically at radiation therapy patients, pooling of available data suggested that use of x3FA-rich nutritional formulas lead to a significant increase in dietary intake of approximately 380 kcal per day when compared with routine care [165]. A closer examination of some individual studies provides clinically useful information.…”
Section: Cachexiamentioning
confidence: 99%
“…A meta-analysis on the influence of nutritional support on adverse outcomes in cancer patients, showed no advantage for the intervention arms [37]. It was noted that the lack of effect might be attributed to poor study designs and heterogeneous patient populations.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The use of nutritional interventions in order to improve these outcomes has not been clearly established yet [35,37,38]. A meta-analysis on the influence of nutritional support on adverse outcomes in cancer patients, showed no advantage for the intervention arms [37].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%